2000
DOI: 10.1007/s003390051060
|View full text |Cite
|
Sign up to set email alerts
|

Structural, optical and electrical properties of ZnO and ZnO-Al 2 O 3 films prepared by dc magnetron sputtering

Abstract: ZnO and ZnO-Al 2 O 3 thin films were prepared by dc magnetron sputtering and their structural, optical and electrical properties were studied comparatively. It is discovered that the ZnO-Al 2 O 3 thin films remain transparent in a shorter wavelength range than the ZnO films, resulting from the increase of their band gap. Their resistivity decreases by seven orders of magnitude, which is caused by doping of Al to ZnO grains in the film. Preferential orientation of ZnO grains in the ZnO-Al 2 O 3 thin films deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Aluminum-doped zinc-oxide (AZO) films have been intensively investigated in recent years because their electrical properties make them suitable for a wide range of applications [1][2][3][4][5]. A number of different methods are currently used to fabricate AZO thin films, the most common being magnetron sputtering [6,7], pulsed laser deposition [8], chemical vapor deposition [9], chemical spray deposition [10], pulsed laser deposition (PLD) [11], and atomic layer deposition (ALD) [12][13][14][15][16]. Magnetron reactive sputtering with a Zn-Al alloy target provides advantages related to target fabrication and film deposition rate [17].…”
Section: Introductionmentioning
confidence: 99%
“…Aluminum-doped zinc-oxide (AZO) films have been intensively investigated in recent years because their electrical properties make them suitable for a wide range of applications [1][2][3][4][5]. A number of different methods are currently used to fabricate AZO thin films, the most common being magnetron sputtering [6,7], pulsed laser deposition [8], chemical vapor deposition [9], chemical spray deposition [10], pulsed laser deposition (PLD) [11], and atomic layer deposition (ALD) [12][13][14][15][16]. Magnetron reactive sputtering with a Zn-Al alloy target provides advantages related to target fabrication and film deposition rate [17].…”
Section: Introductionmentioning
confidence: 99%
“…Thickness‐induced blue shifts in the optical band gaps of Al–Zn–O films have also been reported, partly attributed to an increase in the atomic percent of the aluminum and oxygen contents . Furthermore, it has been observed that the optical band gap of ZnO films shifts toward lower wavelengths as the films are alloyed with Al 2 O 3 …”
Section: Resultsmentioning
confidence: 89%
“…The II‐VI compound semiconductor, zinc oxide, has garnered great attention due to its promising properties for blue/UV optoelectronics, transparent electronics, and UV‐shielding materials . In addition, it has been observed that the optical characteristics of zinc oxide can be modified by dint of alloying it with other materials such as aluminum oxide . This may offer a solution to design a transparent window for effective UV‐B protection of plants.…”
Section: Introductionmentioning
confidence: 99%
“…This balanced electrical and optical properties of TCO makes it useful for a wide range of applications in flat-panel displays, solar cells, gas sensors, thin film transistor (TFT), liquid crystal displays (LCD), photovoltaic devices, organic light emitting diodes (OLEDs) and smart windows. [3][4][5][6][7][8] TCO films can be deposited by different deposition techniques such as spray pyrolysis, [9] solgel process, [10] pulsed laser deposition, [11] thermal evaporation, [12] chemical vapor deposition, [13] electron beam deposition [14] and radio frequency (RF) magnetron sputtering [15][16][17] on various substrate. Among different deposition techniques RF magnetron sputtering technique is more beneficial due to its uniformity and high deposition rates.…”
Section: Introductionmentioning
confidence: 99%